Cognitive dissonance-based eating disorder prevention: pilot study of a cultural adaptation for the Orthodox Jewish community. Issue 2 (4th March 2021) - Casasnovas, Arielle F.; Huryk, Kathryn M.; Levinson, Devorah; Markowitz, Sara; Friedman, Shoshana; Stice, Eric; Loeb, Katharine L.
ABSTRACT: The Body Project (BP) is a cognitive dissonance-based eating disorders (ED) prevention program that targets thin-ideal internalization and reduces ED risk factors and onset for higher-risk adolescent/young adult females. Although the more insular Orthodox Jewish communities reduce exposure to mainstream secular media, they are not immune to thin-ideal internalization and EDs. The present uncontrolled study evaluated the preliminary effects of a cultural adaptation of the BP for Orthodox Jewish girls. The modified manual improved fit with ultra-Orthodox Jewish norms, practices, and values. Eighty-nine 11th-graders in a private, all-female religious high school participated. ED risk factors and symptoms were assessed at baseline, end of 4-week intervention, and 6-month follow-up. Multi-level modeling showed that body dissatisfaction and negative affect significantly decreased across time. Findings demonstrate potential for the BP to be adapted for and implemented in cultural and religious communities wherein interactions with societal influences on thin-ideal internalization differ from dominant culture.